1977
DOI: 10.1126/science.877584
|View full text |Cite
|
Sign up to set email alerts
|

Interferon: An Inducer of Macrophage Activation by Polyanions

Abstract: Purified mouse fibroblast interferon (IF) directly rendered resting macrophages tumoricidal. The physicochemical properties and species specificity of the stimulatory agent fall within the present definition of IF. Since a number of polyanions induce macrophage IF, the antitumor and antimicrobial activities may result from the ability of newly released IF to modify macrophage activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
4

Year Published

1980
1980
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(61 citation statements)
references
References 26 publications
2
55
0
4
Order By: Relevance
“…This induction may be followed by activation of macrophages (17) and augmentation of NK activity through the action of the induced IFN (2). A recent report, how-ever, states that GL is also effective against alcoholic hepatitis (9).…”
mentioning
confidence: 99%
“…This induction may be followed by activation of macrophages (17) and augmentation of NK activity through the action of the induced IFN (2). A recent report, how-ever, states that GL is also effective against alcoholic hepatitis (9).…”
mentioning
confidence: 99%
“…Cumulative evidence indicates that, among their diverse properties, interferons may have a regulatory influence on several immune functions: suppression of lymphocyte proliferation in response to mitogens and alloantigens (LindahlMagnusson et al, 1972a); inhibition in vivo and in vitro of antibody formation to T-cell-dependent and independent antigens (Braun & Levy, 1972;Gisler et al, 1974;Johnson et al, 1975;Sonnenfeld et al, 1977) and enhancement of specific cell-mediated cytotoxicity evoked by tumour-and allo-antigens (Lindahl et al, 1972b;Heron et al, 1976;Zarling et al, 1978). Interferon may also stimulate other effector-cell-mediated mechanisms such as phagocytosis (Huang et al, 1971;Donahoe & Huang, 1976) and nonspecific cytotoxicity (Schultz et al, 1977;Einhorn et al, 1978;Djeu et al, 1979;Senik et al, 1979), act directly on various cell types to inhibit their growth in vitro (Stewart et al, 1976;Balkwill et al, 1978) and modulate the expression of cell surface antigens on lymphocytes and tumour cells (Vignaux & Gresser, 1977).…”
mentioning
confidence: 99%
“…Moreover, we showed in preliminary experiments that natural killer (NK) cell activity in both splenocytes and peritoneal exudate cells derived from SSM-treated mice is higher than in cells from normal control mice. Furthermore, it was reported by Schultz et al (30)(31)(32) that the antitumor activity shown by interferon was mediated by the macrophages activated by the interferon. In addition it was shown by Cantor et al (5) that NK cells may play an important role in prevention of neoplastic growth in hosts.…”
Section: Characterization Of Antiviral Actioity Induced By Ssmmentioning
confidence: 98%